Gonadotropin-releasing hormone agonist protects ovarian function in young patients with ovarian malignancy undergoing platinum-based chemotherapy: A prospective study - Xie, Ya; Duan, Haoran; Wang, Dong; Li, Huiqing; Jia, Jia; Zhang, Jialin; Li, Linlin (Frontiers in Oncology, 2022)
Purpose: We aimed to ascertain the effectiveness of gonadotropin-releasing hormone (GnRH) agonist co-therapy for the preservation of ovarian function in patients with ovarian malignancy who underwent unilateral salpingo-oophorectomy and platinum-based chemotherapy. Methods: We enrolled 158 patients with ovarian malignancy who underwent fertility preservation surgery and postoperative platinum-based chemotherapy between January 2018 and December 2020. Patients were divided into two groups based on the use of GnRH agonist (GnRHa) during chemotherapy. Two patients withdrew from the study. Laboratory tests (serum follicle-stimulating hormone [FSH], serum luteinizing hormone [LH], and serum anti-Müllerian hormone [AMH]) were performed pre-chemotherapy and one year post-chemotherapy. Data on menstruation resumption, perimenopausal symptoms (modified Kupperman Menopausal Index [KMI]), health-related quality of life (Medical Outcomes Study Short Form-36 [MOS SF-36]), and obstetric outcomes were collected. Results: One year post-chemotherapy, the serum AMH level in the GnRHa group was higher than that in the control group (P<0.001), while the serum FSH and FSH/LH levels in the GnRHa group were lower than those in the control group (P<0.001). The mean period from last chemotherapy to menstrual resumption was 3.86 and 5.78 months in the GnRHa and control groups (P<0.001), respectively. The rate of menstrual resumption post-chemotherapy was 93.5% and 82.3% in the GnRHa and control groups (P<0.05), respectively. GnRHa co-administration during chemotherapy reduced the likelihood of low AMH levels post-chemotherapy and was significant in the multivariate analysis (P<0.05). The modified KMI scores and MOS SF-36 scores were better in the GnRHa group than in the control group (both P<0.001). Conclusion: GnRHa protects ovarian function during platinum-based adjuvant chemotherapy in young patients with ovarian malignancy. This study provides a therapeutic reference for gynecologists, especially for those in economically and medically underdeveloped areas. Trial registration: Chinese Clinical Trial Registry (chiCTR1800019114; October 26, 2018; http://www.chictr.org.cn/index.aspx)